2016
DOI: 10.3389/fncel.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100B Protein is Specifically Related to White Matter Changes in Schizophrenia

Abstract: Background: Schizophrenia can be conceptualized as a form of dysconnectivity between brain regions.To investigate the neurobiological foundation of dysconnectivity, one approach is to analyze white matter structures, such as the pathology of fiber tracks. S100B is considered a marker protein for glial cells, in particular oligodendrocytes and astroglia, that passes the blood brain barrier and is detectable in peripheral blood. Earlier Studies have consistently reported increased S100B levels in schizophrenia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 72 publications
(119 reference statements)
1
29
0
Order By: Relevance
“…This MMP9/RAGE mechanism is a primary interest as some evidence implicates MMP9 and RAGE in SZ pathophysiology. For instance, patient serum contains higher levels of AGEs and S100B than serum from healthy controls [76,77]. Different studies have reported conflicting results on the levels of sRAGE in serum, showing increased [30] or decreased sRAGE [77,78] in patient serum.…”
Section: Discussionmentioning
confidence: 99%
“…This MMP9/RAGE mechanism is a primary interest as some evidence implicates MMP9 and RAGE in SZ pathophysiology. For instance, patient serum contains higher levels of AGEs and S100B than serum from healthy controls [76,77]. Different studies have reported conflicting results on the levels of sRAGE in serum, showing increased [30] or decreased sRAGE [77,78] in patient serum.…”
Section: Discussionmentioning
confidence: 99%
“…The antipsychotics haloperidol and risperidone have been shown to be able to inhibit the secretion of S100B in C6 glioma cells following IL-6 stimulation: this result has been interpreted as supporting the involvement of inflammatory processes in schizophrenia (de Souza et al 2013). As an indirect indication that S100B may be involved in processes associated with structural brain changes in schizophrenia, a relationship between blood S100B levels and alterations in white matter (namely the posterior cingulate bundle and superior longitudinal fasciculus), as obtained from T1-weighted MR-images, has been reported in unmedicated schizophrenia patients (Milleit et al 2016).…”
Section: Psychiatric Disordersmentioning
confidence: 69%
“…As an indirect indication that S100B may be involved in processes associated with structural brain changes in schizophrenia, a relationship between blood S100B levels and alterations in white matter (namely the posterior cingulate bundle and superior longitudinal fasciculus), as obtained from T1‐weighted MR‐images, has been reported in unmedicated schizophrenia patients (Milleit et al . ).…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 97%
“…CSF levels of S100β correlated with white matter injury after pneumococcal meningitis [109] and endotoxin-induced periventricular white matter injury in preterm fetal sheep was associated with higher S100β levels [81]. Reduced tissue expression of S100β was observed in the corpus callosum of schizophrenia patients [110] whereas increased serum levels of S100β directly correlated with white matter injury in schizophrenic patients [111] and in asphyxiated preterm babies [112]. In line with these findings, acutely increased serum levels of S100β were associated with patient mortality and poor acute and chronic outcomes after severe TBI [113119] and were predictive of cognitive function at 4 months after pediatric mild TBI [120].…”
Section: Damage Associated Molecular Patterns (Damps): Mediators Omentioning
confidence: 99%
“…Increased S100β and S100β auto-antibody serum levels were also observed in football players who had experienced repeated sub-concussive events and correlated with white matter changes and cognitive decline [121]. As extracranial sources of S100β do not affect serum levels in humans [122], reduced tissue expression likely reflects increased extracellular release due to pathological conditions [111]. Functionally, S100β inhibition reduced neurodegeneration [123] and S100β −/− mice or antibody-mediated neutralization of S100β attenuated microglial reactivity and improved memory function after experimental TBI [124].…”
Section: Damage Associated Molecular Patterns (Damps): Mediators Omentioning
confidence: 99%